Faith, freedom, and family: new studies in law and religion - Witte, John (Untersuchungen über Recht und Religion, 2021)
Cover -- Title -- Contents -- List of Illustrations -- Preface and Acknowledgments -- Gary S. Hauk - Foreword -- Norman Doe - Introduction -- Faith -- 1 The Educational Values of Studying Law and Religion -- 2 Law, Religion, and Metaphor -- 3 What Christianity Offers to the World of Law -- 4 Faith in Law: The Protestant Reformation of Law and Politics -- 5 The Uses of Law for the Formation of Character: A Classic Protestant Doctrine for Late Modern Societies? -- 6 The Good Lutheran Jurist Johann Oldendorp: Law, Conscience, and Equity -- 7 John Calvin as a French Jurist: Law and Liberty in Geneva -- 8 The Christian Constitutionalism of Johannes Althusius -- 9 The Integrative Christian Jurisprudence of John Selden -- 10 Abraham Kuyper on Family, Freedom, and Fortune -- 11 The Integrative Christian Jurisprudence of Harold J. Berma -- 12 Lenn Goodman vs. John Rawls: Law, Religion, and Reason in a Constitutional Democracy -- 13 Law at the Backbone: The Christian Legal Ecumenism of Norman Doe -- Freedom -- 14 The Right to Religious Freedom in the Western Legal Tradition -- 15 Rights, Resistance, and Revolution in the Western Tradition: Early Protestant Foundations -- 16 Ordered Freedom: Herman Dooyeweerd's Emerging Theory of Rights -- 17 The Right to Self-Defense as Grundnorm: David Little's Integrative Theory of Human Rights -- 18 "To Serve Right and to Right Wrong": Pope Benedict XVI on Human Dignity and Human Rights -- 19 "The Oracle of Religious Liberty": John T. Noonan Jr. and The Lustre of Our Country -- 20 "Fairer Still the Woodlands": Mapping the Free Exercise Forest with Kent Greenawalt -- 21 "That Serpentine Wall of Separation": Philip Hamburger and Daniel Dreisbach on America's Founding Metaphor of Religious Freedom -- 22 "Blessed Are the (Religious) Minorities": Natan Lerner on Religious Freedom Jurisprudence in International Perspective.